Exercise and Glycemic Control: Focus on Redox Homeostasis and Redox-Sensitive Protein Signaling - Parker, Lewan; Shaw, Christopher S.; Stepto, Nigel K.; Levinger, Itamar (Frontiers in Endocrinology, 2017)
Physical inactivity, excess energy consumption, and obesity are associated with elevated systemic oxidative stress and the sustained activation of redox-sensitive stress and mitogen activated protein kinase (SAPK) signaling pathways. Sustained SAPK activation leads to aberrant insulin signaling, impaired glycemic control, and the development and progression of cardiometabolic disease. Paradoxically, acute exercise transiently increases oxidative stress and SAPK signaling, yet post-exercise glycemic control and skeletal muscle function are enhanced. Furthermore, regular exercise leads to the upregulation of antioxidant defense which likely assists in the mitigation of chronic oxidative stress associated disease. In this review, we explore the complex spatio-temporal interplay between exercise, oxidative stress, and glycemic control, and highlight exercise-induced reactive oxygen species and redox-sensitive protein signaling as important regulators of glucose homeostasis.